2022
DOI: 10.3389/fonc.2022.789351
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect of Age in Resected Pancreatic Cancer Patients: A Propensity Score Matching Analysis

Abstract: BackgroundWhile the elderly population account for an indispensable proportion in pancreatic ductal adenocarcinoma (PDAC), these patients are underrepresented in clinical trials. Whether surgery offered the same benefit for elderly patients as that for younger cohort and which factors affected long-term outcome of elderly population remained unclear.AimsThis study aims to evaluate long-term prognosis of elderly PDAC patients (≥70 years old) after surgery and to investigate potential prognostic factors.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Patients under 70 years of age were used as a control group for 70–79- and over 80-year-old patients who had undergone pancreatic resection in curative intention [ 14 ]. Indeed, various studies, especially more recent ones, have found a difference in OS and DSF in younger and older patients after pancreatic resection [ 10 , 28 , 29 , 30 ]. Xu et al evaluated the long-term prognosis of 95 patients older than 70 years with pancreatic adenocarcinoma compared to patients under 70 years of age using propensity score matching.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients under 70 years of age were used as a control group for 70–79- and over 80-year-old patients who had undergone pancreatic resection in curative intention [ 14 ]. Indeed, various studies, especially more recent ones, have found a difference in OS and DSF in younger and older patients after pancreatic resection [ 10 , 28 , 29 , 30 ]. Xu et al evaluated the long-term prognosis of 95 patients older than 70 years with pancreatic adenocarcinoma compared to patients under 70 years of age using propensity score matching.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the undertreatment of older patients is another influential factor [ 36 ]. Even recent studies in pancreatic cancer patients with primary surgical resection presented lower rates of adjuvant chemotherapy in the elderly [ 28 , 37 ], whereas studies showed that adjuvant chemotherapy is associated with prolonged survival independent of age [ 38 ]. The reasons are, therefore, multifactorial, and one must assume that the patient’s general condition was too weak or they refused adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Hackner et al [56] Retrospective .004 Xu et al [57] was associated with a longer median survival (17.2 months; 95% confidence interval [CI], 16.1-19.0) compared with those who did not receive adjuvant chemotherapy (12.7 months; 95% CI, 11.8-13.6) in the elderly PDAC patients (80 years or older) and this association was consistent in propensity and subgroup analyses. [58] Besides, further multivariable analysis indicated receipt of adjuvant chemotherapy (hazard ratio [HR], 0.72; 95% CI, 0.65-0.79; P < .001) was associated with a decreased hazard of death in the elderly PDAC patients.…”
Section: Safety Feasibility and Effect Of Chemotherapy In Elderly Pda...mentioning
confidence: 79%
“…In our study, we found that the main age group of PCLM patients was between 50 and 74 years. According to the Kaplan–Meier survival analysis, the prognosis of older patients had worse OS compared with younger patients [ 66 , 67 ]. This confirms earlier findings that older patients could be more susceptible to tumor immune escape as their autoimmune capacity decreases [ 68 ].…”
Section: Discussionmentioning
confidence: 99%